A novel integrated sequential air flotation in cold-rolling emulsion wastewater (CREW) treatment: Satisfying oil droplets growth laws at various stages. (August 2022) - Wei, Linghui; Li, Meng; Gao, Feng; Zhang, Yibo; Li, Chengwei; Zhang, Qian
Abstract: The traditional air flotation device with a single structure cannot fully satisfy the requirements of oil droplets growth at different conglomeration stages in CREW (cold-rolling emulsion wastewater) treatment, thus leading to relatively poor demulsification effect. To address this concern, a novel integrated sequential air flotation device was carved out. Besides, two kinds of organic and inorganic demulsifiers were collectively used in sequence to give full play to the advantages of this device. The optimal operating conditions were determined by single factor experiments and response surface analysis and the performance of the entire device was evaluated. The possible demulsification mechanism was investigated by FITR and GCMS results for CREW, the interfacial tension (IFT), membrane rupture rate and micrograph observation. In the actual wastewater treatment, the COD removal efficiency increased from 93% to 98% compared with a single air flotation device. This research provides theoretical guidance for the metallurgy emulsion treatment. Graphical abstract: A novel integrated sequential air flotation device was carved out. Besides, two kinds of organic and inorganic demulsifiers were collectively used in sequence to give full play to the advantages of this device. Unlabelled Image Highlights: Integrated flotation device met the growth laws of oil droplets in various stages. Effect of the compound demulsifiers was explored by response surface analysis. Synergistic mechanism of two demulsifiers to design an integrated flotation device.